Female sex workers' use of mobile phones in India: Lessons in effective engagement - Panchanadeswaran, Subadra; Unnithan, Ardra; Chacko, Shubha; Brazda, Michael; Wilson, Natalie; Kuruppu, Santushi (Human Technology, 2019)
Despite the widespread impact of mobile phone technology, research on female sex workers’ (FSWs) access and use of this technology is sparse. This study aimed to document FSWs’ subjective perceptions of the benefits of mobile phone technology as well as examine the potential for its use by nongovernmental organizations (NGOs). Employing a phenomenological study built on in-depth qualitative interviews and focus group discussions with 67 FSWs and 18 staff and leaders from local NGOs in Mumbai and various locations of the Karnataka State in India between January and May 2015. Findings revealed complex trajectories for FSWs regarding accessing, learning about, and using mobile phone technology. FSW participants highlighted enhanced social connectedness with clients and their communities while NGO personnel underscored the newer ways of engagement with FSWs with mobile phone technology. Study findings point to both opportunities and challenges posed by FSWs’ extensive use of mobile phone technology.